KEHIDUPAN REMAJA PERKOTAAN DALAM NOVEL TEENLITE THE UNFUNNIEST COMEDY KARYA WIWIEN WINTARTO - Jayawardana, Mahawitra; WS, Hasanuddin; Hayati, Yenni (Universitas Negeri Padang, 2018)
The purpose of this study is to describe the representation of (1) personality pleasure, (2) recreational prestige, (3) group fun, (4) juvenile delinquency, (5) hypoactivism, and (6) urban teenage cultures in a teen lite novel, The Unfunniest Comedy by Wiwien Wintarto. The data are the phrase, clause, sentence, that shown a problem of urban teenage life in a teen lite novel, The Unfunniest Comedy by Wiwien Wintarto. The results of the study are (1) the representation of personality pleasures in novel is depicted by reading tabloids and watching movies, (2) the representation of recreational prestige in a novel are teenagers shopping activities, houses in residential areas, luxury restaurants is visited for meals, their owned vehicles , cinema as a place of entertainment that must be visited, and work in the entertainment industry, (3) the representation of group fun in a novel are teenagers who can be told an opinion in a group and set up rules in association, (4) the representation of juvenile delinquency in a novel is against the status of skipping school and leaving training obligations, (5) the representation of hypoaktivism in a novel is teenagers’ dependency on others in daily activity, (6) the representation of cultural in this novel is teenagers’ behavior that mimics their idol. Keywords: novel, teenlit, urban teenagers